Powering Up : Costing Power Infrastructure Spending Needs in Sub-Saharan Africa - Rosnes, Orvika (World Bank, Washington, DC, 2017)
Sub-Saharan Africa will require substantial investments in the power sector on the order of 4 percent of the region's gross domestic product (GDP) annually before 2015 if it is to meet the demands of economic development, keep pace with population growth, and expand electrification beyond the 2005 regional average of just 34 percent. Developing a regional power-trading market that exploits the vast hydropower potential of the subcontinent may be the best way to bring those costs down while also protecting against increases in oil prices and curbing carbon emissions. Expanding electrification is a daunting challenge, but the costs associated with extending the transmission network are minor in comparison with the investments in generation needed to accompany the demand of Africa's growing economies.